Photocatalytic Semi-Hydrogenation of Alkynes: A Game of Kinetics, Selectivity and Critical Timing - Melissa Cely-Pinto; Bowen Wang; Juan C. Scaiano (Nanomaterials, 2023)
The semi-hydrogenation reaction of alkynes is important in the fine chemicals and pharmaceutical industries, and it is thus important to find catalytic processes that will drive the reaction efficiently and at a low cost. The real challenge is to drive the alkyne-to-alkene reaction while avoiding over-hydrogenation to the saturated alkane moiety. The problem is more difficult when dealing with aromatic substitution at the alkyne center. Simple photocatalysts based on Palladium tend to proceed to the alkane, and stopping at the alkene with good selectivity requires very precise timing with basically no timing tolerance. We report here that the goal of high conversion with high selectivity could be achieved with TiO2-supported copper (Cu@TiO2), although with slower kinetics than for Pd@TiO2. A novel bimetallic catalyst, namely, CuPd@TiO2 (0.8% Cu and 0.05% Pd), with methanol as the hydrogen source could improve the kinetics by 50% with respect to Cu@TiO2, while achieving selectivities over 95% and with exceptional timing tolerance. Further, the low Palladium content minimizes its use, as Palladium is regarded as an element at risk of depletion.